2008
DOI: 10.4049/jimmunol.180.9.6018
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus Activates Human Dendritic Cells to Promote Innate Antitumor Immunity

Abstract: Oncolytic viruses can exert their antitumor activity via direct oncolysis or activation of antitumor immunity. Although reovirus is currently under clinical investigation for the treatment of localized or disseminated cancer, any potential immune contribution to its efficacy has not been addressed. This is the first study to investigate the ability of reovirus to activate human dendritic cells (DC), key regulators of both innate and adaptive immune responses. Reovirus induced DC maturation and stimulated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
175
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(188 citation statements)
references
References 49 publications
9
175
1
Order By: Relevance
“…110,111 Although tumor-infiltrating DCs were impaired at maturation by immunosuppressive IL-10, PGE 2 , and transforming growth factor b produced from tumor cells, 112 unidentified components in the culture media from reovirus-infected cancer cells facilitated maturation of DCs. 113 Recent studies delineated that oncolytic viruses such as vaccinia, measles, HSV-2, and adenovirus cause the release of HMGB1. 64,65,114,115,116,117 Although HMGB1 interacts with viral components and may modulate viral replication, 117 the molecular mechanisms of how each oncolytic virus differentially produces these DAMPs remain largely elusive.…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 99%
“…110,111 Although tumor-infiltrating DCs were impaired at maturation by immunosuppressive IL-10, PGE 2 , and transforming growth factor b produced from tumor cells, 112 unidentified components in the culture media from reovirus-infected cancer cells facilitated maturation of DCs. 113 Recent studies delineated that oncolytic viruses such as vaccinia, measles, HSV-2, and adenovirus cause the release of HMGB1. 64,65,114,115,116,117 Although HMGB1 interacts with viral components and may modulate viral replication, 117 the molecular mechanisms of how each oncolytic virus differentially produces these DAMPs remain largely elusive.…”
Section: Damps Induced By Infection With Oncolytic Virusesmentioning
confidence: 99%
“…Reovirus-initiated cytokine response in vitro has previously been reported (38,39); however, the comprehensive profile of such a response in different immune cell subsets or in vivo is still obscure. Using Antibody-based Quantitative (and Qualitative) Cytokine Array, we evaluated the expression of 60 cytokines following reovirus exposure of BMDCs, lymphocytes, and tumor cells in vitro or immunocompetent and immunocompromised mice in vivo.…”
Section: Reovirus Induces Proinflammation Lymphoid Cell Migration Dmentioning
confidence: 99%
“…Native B16 melanoma (B16) and Lewis lung carcinoma (LLC) were purchased from the American Type Culture Collection, whereas ovalbumin (ova)-expressing B16 (B16-ova; ref. Antibodies and reagents used in this study were purchased from different manufacturers as follows: eBioscience: Alexa 488-anti-CD11c, PE-anti-CD86, APCanti-CD40, APC-anti-CD80, PE-anti-mouse MHC class I molecule Kb bound to the peptide SIINFEKL (25-D1.16), unconjugated anti-mouse CD16/32, and unconjugated anti-mouse CD49d; Invitrogen: PE-anti-CD3, Alexa 488-IFN-γ, APC-anti-CD107a, unconjugated anti-mouse CD28, and 5-(and-6)-carboxyfluorescein diacetate (CFSE); BioLegend: PerCp-anti-MHC class II (H-2A/E) and PerCp-anti-CD90.2; BD Biosciences: PerCp-anti-CD8; GenScript: SIINFEKL (ova [257][258][259][260][261][262][263][264] ) and KAVYNFATM (LCMV gp [33][34][35][36][37][38][39][40][41] ) peptides.…”
Section: Reovirus Cell Lines and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, recent report studying the reovirus-induced immune responses during clinical trials showed increased number of CD3-CD56+ NK cells in the peripheral bloood mononuclear cells (PBMC) of the reovirus-treated patients (56). After culture with reovirus type 3 Dearing strain, human myeloid DC generated from PBMC get activated, produce proinfla-mmatory cytokines, e.g., IFN-α/β, TNF-α, IL-12 and IL-6, and further enhance the anti-tumor cytotoxic potential of NK as well as T cells (18). These studies have confirmed the ability of reovirus to stimulate different components of innate immunity.…”
Section: Immunological Aspects Of Reo-virus Oncolysismentioning
confidence: 99%